First records of three genera, Cyphomella Sæther, 1977, Olecryptotendipes Zorina, 2007 and Robackia Sæther, 1977 of the Harnischia complex from India with description of O. extentus sp. n., O. obtunsus sp. n. and R. aequilongia sp. n. (Diptera: Chironomidae) - Mukherjee, Bindarika; Hazra, Niladri (Zootaxa, 2022)
Three genera, Cyphomella Sæther, 1977, Olecryptotendipes Zorina, 2007 and Robackia Sæther, 1977, of the Harnischia complex are recorded for the first time from India. Two new species of Olecryptotendipes and one new species of Robackia are described on the basis of adult males. Cyphomella camelus (Kieffer, 1955), described from Afrotropical and Palaearctic regions, is recorded for the first time from India and its description is supplemented. The molecular barcodes of three species, O. obtunsus sp. n., C. camelus and R. aequilongia sp. n., are also provided. Revised world keys to the adult males of the Olecryptotendipes and Robackia are also provided.